Pengaruh Latihan Ladder Drill Dan Dot Drill Terhadap Kelincahan Tendangan T di UKM Pencak Silat Tapak Suci Universitas Muhammadiyah Sukabumi - Riska Rahayu; Wening Nugraheni; Muhammad Saleh (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This research was conducted to determine the agility of the T-kick of the female fighter of the Tapak Suci UKM, Muhammadiyah University, Sukabumi. Researchers carried out this research using quantitative methods (Pretest-Postest Group Design). The population in this study were members of the Tapak Suci UKM, Muhammadiyah University of Sukabumi, the samples in this study were 8 female fighters. This study uses a purposive sampling technique taken from gender criteria, namely women. The instruments used are (1) the training program, (2) the T kick agility test. Based on the data analysis carried out, this study has a significant effect, it can be seen from the paired sample t test, thesignificance value is ladder drill 0.001 with a significance level < 0, 05, and the acquisition of thesignificance of dot drill 0.002 with a significance level of <0.05, which means that in this study there was an effect of training using ladder drills and dot drills on T-kick agility in Tapak Suci UKM, Muhammadiyah University of Sukabumi.